Seismic behavior of corroded RC slab column connection - Nicolaus Syaiful (Nanyang Technological University, 2022)
Reinforced Concrete is one of the most used building materials in the world, with concrete being extremely strong in compressive strength and steel rebars complimenting the lacking tensile strength, making a well-rounded material. Corrosion is one of the most seen long-term deteriorating effects on Reinforced Concrete and it is described thoroughly with examples on how the corrosion affects the integrity and ultimate strength capacity of the connections and concrete. The slab-column connection is commonly used to distribute the load from the slab to the column and to withstand gravity load and rarely used for seismic forces. The slab-column connection is susceptible to punching failure, where there is localised force acting on the connection. This final year project experiments on corroded and uncorroded slab- column connections and analyses the experimental and analytical data using DIANA. DIANA was used to simulate the behaviour of Reinforced Concrete slab-column connections under the loadings. Various research papers were validated in DIANA to test the accuracy of the simulation software. The method for making a specimen for testing seismic behaviours are also described.